Immediate versus delayed postpartum insertion of contraceptive implant for contraception - Sothornwit, Jen (Cochrane Database Syst Rev, 2017)
BACKGROUND: The spacing of pregnancies has a positive impact on maternal and newborn health. The progestin contraceptive implant, which is a long‐acting, reversible method of contraception, has a well‐established low failure rate that is compatible with tubal sterilization. The standard provision of contraceptive methods on the first postpartum visit may put some women at risk of unintended pregnancy, either due to loss to follow‐up or having sexual intercourse prior to receiving contraception. Therefore, the immediate administration of contraception prior to discharge from the hospital that has high efficacy may improve contraceptive prevalence and prevent unintended pregnancy. OBJECTIVES: To compare the initiation rate, effectiveness, and side effects of immediate versus delayed postpartum insertion of implant for contraception. SEARCH METHODS: We searched for eligible studies up to 28 October 2016 in the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, and POPLINE. We examined review articles and contacted investigators. We also checked registers of ongoing clinical trials, citation lists of included studies, key textbooks, grey literature, and previous systematic reviews for potentially relevant studies. SELECTION CRITERIA: We sought randomised controlled trials (RCTs) that compared immediate postpartum versus delayed insertion of contraceptive implant for contraception. DATA COLLECTION AND ANALYSIS: Two review authors (JS, YW) independently screened titles and abstracts of the search results, and assessed the full‐text articles of potentially relevant studies for inclusion. They extracted data from the included studies, assessed risk of bias, compared results, and resolved disagreements by consulting a third review author (PL or SK). We contacted investigators for additional data, where possible. We computed the Mantel‐Haenszel risk ratio (RR) with 95% confidence interval (CI) for binary outcomes and the mean difference (MD) with 95% CI for continuous variables. MAIN RESULTS: Three studies that included 410 participants met the inclusion criteria of the review. We did not identify any ongoing trials. Two included studies were at low risk of selection, attrition, and reporting biases, but were at high risk of performance and detection biases due to the inability to blind participants to the intervention. One included study was at high risk of attrition bias. The overall quality of the evidence for each comparison ranged from very low to moderate; the main limitations were risk of bias and imprecision. Initiation rate of contraceptive implants at the first postpartum check‐up visit was significantly higher in the immediate insertion group than in the delayed insertion group (RR 1.41, 95% CI 1.28 to 1.55; three studies, 410 participants; moderate quality evidence). There appeared to be little or no difference between the groups in the continuation rate of contraceptive implant used at six months after insertion (RR 1.02, 95% CI 0.93 to 1.11; two studies, 125 participants; low quality evidence) or at 12 months after insertion (RR 1.04; 95% CI 0.81 to 1.34; one study, 64 participants;very low quality evidence) Women who received an immediate postpartum contraceptive implant insertion had a higher mean number of days of abnormal vaginal bleeding within six weeks postpartum (MD 5.80 days, 95% CI 3.79 to 7.81; one study, 215 participants; low quality evidence) and a higher rate of other side effects in the first six weeks after birth (RR 2.06, 95% CI 1.38 to 3.06; one study, 215 participants; low quality evidence) than those who received a delayed postpartum insertion. There appeared to be little or no difference between the groups in heavy, irregular vaginal bleeding or associated severe cramping within 12 months (RR 1.01, 95% CI 0.72 to 1.44, one study, 64 participants;very low quality evidence). It was unclear whether there was any difference between the groups in scores for participant satisfaction on a 0‐10 scale (MD ‐0.40, 95% CI ‐1.26 to 0.46, low quality evidence), or in rates of unintended pregnancy (RR 1.82, 95% CI 0.38 to 8.71, 1 RCT, 64 women, very low quality evidence) at 12 months, or in rate of breastfeeding rate at six months (RR 2.01, 95% CI 0.72 ro 5.63, 1 RCT, 64 women, very low quality evidence) rate did not differ significantly between the groups. AUTHORS' CONCLUSIONS: Evidence from this review indicates that the rate of initiation of contraceptive implant at the first postpartum check‐up visit was higher with immediate postpartum insertion than with delayed insertion. There appeared to be little or no difference between the groups in the continuation rate of contraceptive implant use at 6 months. It was unclear whether there was any difference between the groups in continuation of contraceptive use at 12 months or in the unintended pregnancy rate at 12 months.